2009
DOI: 10.1144/sp311.5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evolution of the North Anatolian Fault: new constraints from its eastern termination

Abstract: The deformation and 40Ar–39Ar dating of recent volcanism, that remarkably sits across the North Anatolian Fault eastern termination in Turkey, together with previous studies, put strong constraints on the long-term evolution of the fault. We argue that after a first phase of 10 Ma, characterized by a slip rate of about 3 mm/a, and during which most of the trace was established, the slip rate jumped to about 20 mm/a on average over the last 2.5 Ma, without substantial increase of the fault length. The transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 70 publications
2
89
0
1
Order By: Relevance
“…The previously postulated relation to Anatolian extrusion (which is largely younger than early Pliocene [Hubert-Ferrari et al, 2009]) by, e.g., Taymaz et al [1991] and Kissel et al [2003] is shown in section 6.1 to be an unlikely candidate as well. The shortening we infer east of the west Anatolian pivot point ( Figure 10) rather suggests that around 16 Ma the central segment of the Isparta Angle underwent shortening together with Africa.…”
Section: Kinematic and Geodynamic Implicationsmentioning
confidence: 89%
“…The previously postulated relation to Anatolian extrusion (which is largely younger than early Pliocene [Hubert-Ferrari et al, 2009]) by, e.g., Taymaz et al [1991] and Kissel et al [2003] is shown in section 6.1 to be an unlikely candidate as well. The shortening we infer east of the west Anatolian pivot point ( Figure 10) rather suggests that around 16 Ma the central segment of the Isparta Angle underwent shortening together with Africa.…”
Section: Kinematic and Geodynamic Implicationsmentioning
confidence: 89%
“…10. Summary of the evolution of the triple junction between the Arabian, Eurasian, and Anatolian plates (from Arger et al, 1996;Westaway andArger, 1996, 2001;Hubert-Ferrari et al, 2009) …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…18; 17), which is a major tributary of the Euphrates River, is deflected by the NAFZ for approximately 60 km (Şengör et al, 2005). The easternmost offset measurement is the offset of the Bingöl Volcano by approximately 50 km in 2.5 Ma as proposed in a recent study (Hubert-Ferrari et al, 2009), which is attributed to long-term activity of the NAFZ-Varto Fault ( Fig. 18; 18).…”
Section: Comparison Of the Results With Past Cumulative Offset Estimamentioning
confidence: 66%
“…These are discussed critically and selectively used by previous authors to prove the model initiation age (Barka, 1992;Westaway, 1994;Armijo et al, 1999;Yaltırak, 2002) and evolutionary models (Şengör, et al, 2005) of the whole NAFZ system. There is an ongoing discussion about whether the NAFZ formed in the east and propagated to the west over time (10-12 Ma from east to~5 Ma at west; Şengör, 1979;Barka, 1992;Westaway, 1994;Armijo et al, 1999;Şengör et al, 2005) or whether the opposite occurred (Chorowicz et al, 1999;Adıyaman et al, 2001), and whether the slip/propagation rate accelerated Şengör et al, 2005;Hubert-Ferrari et al, 2009) or remained constant (Westaway, 1994;Armijo et al, 1999;Reilinger et al, 2006). New evidence indicates that there is dextral strike-slip faulting in the western Anatolia pre-dating the Miocene Arabia-Eurasia collision and Late Miocene-Early Pliocene NAFZ (Zattin et al, 2005;Okay et al, 2010).…”
Section: Comparison Of the Results With Past Cumulative Offset Estimamentioning
confidence: 99%